“A Correlation Study of Core Muscle Strength with Rectus Femoris Flexibility in Obese and Nonobese Patients with Knee Osteoarthritis”: An Observational Study - Manalisa Kalita; Sunita Sharma (Journal of the Scientific Society)
Context: Knee osteoarthritis (KOA) is a common impairment, particularly in women and older individuals, often exacerbated by obesity. However, the potential correlation between rectus femoris flexibility and core muscle strength in KOA patients lacks sufficient evidence and warrants further investigation. Aims: The study evaluates core muscle strength and rectus femoris flexibility in obese and nonobese KOA patients through a single-center observational study to determine their association. Settings and Design: MMIPR orthopedics outpatient department and cross-sectional study were conducted. Subjects and Methods: Participants aged 40–70 meeting inclusion/exclusion criteria were selected (n = 51). Divided by body mass index (BMI) into obese and nonobese groups, core strength was measured with a pressure biofeedback unit, rectus femoris flexibility with Ely’s test, and pain intensity with Visual Analog Scale. Statistical Analysis Used: Data were analyzed using SPSS 20. Normality confirmed through Kolmogorov–Smirnov’s test (sample size >50). Descriptive stats are presented as mean ± standard deviation significance set at P < 0.05. Between group analysis via Mann-Whitney U-test due to not normally distribution. Correlation analyzed with Spearman's rank test for not narmally distributed data. Results: A positive correlation was found between core muscle strength and rectus femoris flexibility in obese patients with OA knee. However, no significant correlation was found between the core muscle strength with rectus femoris flexibility in nonobese patients with KOA. Conclusions: This study found that in obese individuals with OA knee, core muscular strength is favorably correlated with rectus femoris muscle flexibility. However, there is a negative correlation between BMI and core muscle strength.